تأثير فهم القواعد النحوية في مهارة قراءة التفسير للطالبات المكثفة في المستوى الثامن "أ" بجامعة الأمين الإسلامية برندوان سومنب مادورا للعام الدراسي 2021- 2022 م - Uswatun Hasanah; Nurul Istiqomah (Nady Al-Adab : Jurnal Bahasa Arab, 2022)
The purpose of this research is to knowing the effect of understanding grammatical rules on the reading skill of the intensive students at VIII semester "A" at Al-Amien Prenduan For Islamic Studies Sumenep Madura period 2021-2022 AD, and to find out how much the effect of understanding the grammatical rules on the reading skill of the intensive at VIII semester "A" at Al-Amien Prenduan For Islamic Studies Sumenep Madura period 2021-2022 AD. The research sample consisted of 28 female students. This research uses quantitative research, data collection method in the form of testing and documentation. The data analysis method used means simple linear regression analysis. Thus, the coefficient of determination is 0.778, which means that the effect of grammar understanding (X) reading skill interpretation (Y) is 77.8% and the rest is affected by other variables outside this research. The results of the homogeneity test mean Ftable ≤ Fcount or 4.23 ≤ 102.22. Thus, the influence of grammatical understanding on the skill of reading interpretation has a significant direction.